Study on the Effectiveness of Herbal Medicine for Endometriosis - Somia Al-Tahouni,; Farah Emagrahi,; Abd Alrahim Shatawh, (AlQalam Journal of Medical and Applied Sciences, 2025)
Endometriosis is a condition characterized by the growth of endometrial-like tissue outside the uterine cavity, typically occurring in the lower abdomen or pelvic region. This condition affects approximately 8-10% of women of reproductive age, with its prevalence rising to about 40-50% among women experiencing infertility. It is a chronic disease that causes severe pelvic pain, inflammation, and increases the risk of miscarriage, preterm birth, and severe hemorrhage during delivery. Numerous studies have highlighted the potential of alternative herbal treatments, emphasizing their role due to properties such as antioxidant, anti-inflammatory, and anti-angiogenic effects. This current study was based on field visits to the Al-Yaqeen Center in the city of Tripoli. A questionnaire was designed to collect data from patients. The study included a sample of 30 married women with endometriosis, spanning different age groups: Group 1 (20-25 years), Group 2 (25-30 years), Group 3 (30-35 years), and Group 4 (35 years and above). The study's temporal scope was the period from May 29, 2024, to January 30, 2025. The highest proportion of participants was in the age group of 35 years and above (47%), while the lowest proportion was in the 20-25 years age group (10%). A statistically significant difference was observed between the age groups, with a p-value of 0.047, which is below the significance level of 0.05. Regarding treatment duration, the highest proportion received treatment for 3-4 months (43%), whereas the lowest proportion was for a treatment duration of (1-2) months at a rate of (20%), with no statistically significant differences found for the treatment duration (p-value = 0.073). The highest rate concerning years of infertility was (6-11) years at (47%), while the lowest rate was (12 years or more) at (23%), with a statistically significant difference (p-value = 0.018). The objectives of this study are to define the disease, raise awareness among women about its risks, and encourage early diagnosis due to its negative consequences. Furthermore, it aims to highlight the effectiveness of medicinal herbs. Herbal treatments typically involved formulations ranging from 10 to 20 components, with the use of some demonstrating effectiveness in alleviating pain, inhibiting tissue migration, and reducing estrogen production.